Structural basis for binding the TREX2 complex to nuclear pores, GAL1 localisation and mRNA export. Issue 10 (4th April 2014) - Jani, Divyang; Valkov, Eugene; Stewart, Murray
Abstract : The conserved Sac3:Thp1:Sem1:Sus1:Cdc31 (TREX2) complex binds to nuclear pore complexes (NPCs) and, in addition to integrating mRNA nuclear export with preceding steps in the gene expression pathway, facilitates re-positioning of highly regulated actively transcribing genes (such as GAL1 ) to NPCs. Although TREX2 is thought to bind NPC protein Nup1, defining the precise role of this interaction has been frustrated by the complex pleiotropic phenotype exhibited by nup1Δ strains. To provide a structural framework for understanding the binding of TREX2 to NPCs and its function in the gene expression pathway, we have determined the structure of the Nup1:TREX2 interaction interface and used this information to engineer a Sac3 variant that impairs NPC binding while not compromising TREX2 assembly. This variant inhibited the NPC association of both de-repressed and activated GAL1 and also produced mRNA export and growth defects. These results indicate that the TREX2:Nup1 interaction facilitates the efficient nuclear export of bulk mRNA together with the re-positioning of GAL1 to NPCs that is required for transcriptional control that is mediated by removal of SUMO from repressors by NPC-bound Ulp1.